2017
DOI: 10.3390/catal7050157
|View full text |Cite
|
Sign up to set email alerts
|

Development of Active and Stable Low Nickel Content Catalysts for Dry Reforming of Methane

Abstract: Methane dry reforming (DRM) was investigated over highly active Ni catalysts with low metal content (2.5 wt %) supported on Mg-Al mixed oxide. The aim was to minimize carbon deposition and metal sites agglomeration on the working catalyst which are known to cause catalyst deactivation. The solids were characterized using N 2 adsorption, X-ray diffraction, temperature-programmed reduction, X-ray photoelectron spectroscopy, and UV-Vis diffuse reflectance spectroscopy. The results showed that MgO-Al 2 O 3 solid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 56 publications
(91 reference statements)
3
22
0
Order By: Relevance
“…This effect is attributed to the presence of La that promotes the oxygen mobility and/or formation of defect structures where MgO is doped with Ni 2+ . On the other side,sample La.Ni(CA)/Mg 1.3 AlO x .1000 exposes the β peak at a temperature similar to that of La.Ni(CA)/Mg 1.3 AlO x and an additional split γ peak at very high temperature (980 °C) assigned to Ni in strong interaction with the support …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This effect is attributed to the presence of La that promotes the oxygen mobility and/or formation of defect structures where MgO is doped with Ni 2+ . On the other side,sample La.Ni(CA)/Mg 1.3 AlO x .1000 exposes the β peak at a temperature similar to that of La.Ni(CA)/Mg 1.3 AlO x and an additional split γ peak at very high temperature (980 °C) assigned to Ni in strong interaction with the support …”
Section: Figurementioning
confidence: 99%
“…[12,24] On the other side,sample La.Ni (CA)/Mg 1.3 AlO x .1000 exposes the β peak at a temperature similar to that of La.Ni(CA)/Mg 1.3 AlO x and an additional split γ peak at very high temperature (980°C) assigned to Ni in strong interaction with the support . [25] These β and γ Ni 2 + species are poorly reduced in usual pretreatment and therefore La.Ni(CA)/Mg 1.3 AlO x .1000 is only partially reduced before DRM. The Ni metal fraction after in situ reduction was evaluated in a two-step experiment: first, the reduction at 700°C was made, directly followed by a regular TPR experiment up to 1000°C.…”
mentioning
confidence: 99%
“…Tu et al's contribution on palladium catalysts supported on titania for hydrogen peroxide production [16] also touches on themes of this metal and support in Dr. Bartholomew's work. Ha et al's paper on nickel catalysts for (dry) methane reforming and carbon deactivation [17] go back to Dr. Bartholomew's early work on both nickel and methane reforming. Türks et al's work on CO 2 methanation on nickel catalysts builds on these major themes of Dr. Bartholomew's research [18].…”
Section: The Contents Of the Special Issuementioning
confidence: 99%
“…It is reported that the insertion of nickel into a well-defined structure, like the perovskites [8], hexaaluminates [9], spinels [10] or in a solid solutions [11], can reduce its deactivation. In dry reforming reaction, the active site is metallic transition metal [12].…”
Section: Introductionmentioning
confidence: 99%